Multi‐institutional retrospective study for the evaluation of ocular function–preservation rates in maxillary sinus squamous cell carcinomas with orbital invasion. Issue 4 (9th April 2014) - Sakashita, Tomohiro; Hayashi, Ryuichi; Homma, Akihiro; Matsuura, Kazuto; Kato, Kengo; Kawabata, Kazuyoshi; Monden, Nobuya; Hasegawa, Yasuhisa; Onitsuka, Tetsuro; Fujimoto, Yasushi; Iwae, Shigemichi; Okami, Kenji; et al.
Abstract: Background: The purpose of this retrospective analysis was to evaluate ocular function and survival rates among treatment modalities in patients with maxillary sinus cancer with orbital invasion. Methods: Eighty‐seven patients were classified according to the main treatment modality. Ocular function preservation rates and survival rates were evaluated for each therapeutic modality. Results: The 5‐year overall survival rate for the en bloc resection, conservative surgery, superselective intra‐arterial chemotherapy, and radiotherapy (RADPLAT), intravenous chemoradiotherapy (IV‐CRT) was 70%, 35%, 49%, and 31%, respectively. The ocular function preservation rate for each group was 15%, 27%, 30%, and 17%, respectively. In the en bloc resection group, there was no significant difference in the 5‐year overall survival rate between patients with orbital exenteration and those without orbital exenteration (72% vs 71%; p = .9321). Conclusion: The en bloc resection group showed a favorable survival rate but a low preservation rate. Preservation of orbital contents did not reduce the survival rate. © 2014 Wiley Periodicals, Inc. Head Neck 37 : 537–542, 2015